Elimination of corporal punishment of children's a human right - Stevanović Ivana; Srna Jelena (Temida)
The authors indicate the necessity of explicit legal prohibition of all corporal punishment of children that represent a violation of the right of the child to respect his/her physical integrity and human dignity. The paper emphasizes why all corporal punishment of children should be prohibited and points out the progress made at the legislative level to the elimination of all corporal punishment of children in some member states of the Council of Europe and the Republic of Serbia.